Pengaruh CSR dan Struktur Modal Terhadap Nilai Perusahaan dengan Firm Size Sebagai Variabel Moderasi - Rahmawati, Heni; Susilo, Dwi Ermayanti (Journal of Business and Economics Research (JBE), 2025)
This study examines the influence of Corporate Social Responsibility and capital structure on firm value, with firm size as a moderating variable. This study focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. A descriptive quantitative approach was used with the purposive sampling method. The collection of secondary data obtained from financial reports with a sample of 41 companies in the energy sector. Data analysis was conducted using SPSS version 25.0. The analysis results show that Corporate Social Responsibility has a significant impact on company value with a p-value of 0.042 < 0.050, thus the hypothesis is accepted. Capital structure also has a significant impact with a p-value of 0.036 < 0.050, thus the hypothesis is accepted. The interaction of Corporate Social Responsibility with firm size shows a significant impact with a p-value of 0.043 < 0.050, thus the hypothesis is accepted, with firm size as a moderating variable strengthening the relationship between Corporate Social Responsibility and company value. Similarly, the interaction of capital structure with firm size with a p-value of 0.038 < 0.050, thus the hypothesis is accepted, with firm size as a moderating variable strengthening the relationship between capital structure and company value. These findings indicate that although Corporate Social Responsibility and capital structure are important in enhancing company value, their effectiveness can be influenced by firm size. In the context of the energy sector, large companies face higher expectations regarding Corporate Social Responsibility and complex capital structure management, which can reduce its positive impact on company value. This research provides important implications for energy company management strategies in optimizing Corporate Social Responsibility, capital structure, and considering company size in strategic planning. In the context of the energy sector, large companies face higher expectations regarding Corporate Social Responsibility and complex capital structure management, which can reduce its positive impact on company value. This research provides important implications for energy company management strategies in optimizing Corporate Social Responsibility, capital structure, and considering firm size in strategic planning.